Exploring the Proficiency of English Teachers in Digital Literacy - Sri Arfani; Yanti Rosalinah; Ibnu Subroto; Retno Rahayuningsih; Rina Lestari (STAI Hubbulwathan Duri, 2023)
In the post-pandemic era, teachers must have digital literacy skills to effectively teach and engage with their students in a virtual or hybrid learning environment. One problem with digital literacy and teachers in the post-pandemic era is that not all teachers may have the necessary skills and training to use technology for teaching and learning effectively. Building on these findings, this study aimed to investigate the digital literacy competence of English teachers and address the problems and challenges they face in the post-pandemic era. This study was conducted using a qualitative method with a descriptive analysis approach. The study was conducted in Bogor city, with data collected through a questionnaire administered from 25 English teachers in several senior high schools. The results suggest that most teachers have a high level of digital literacy in using technology to support learning, possibly due to the increasing emphasis on technology integration in education and the availability of professional development opportunities. However, there is still room for improvement in areas such as digital assessment, identifying credible sources, and recognizing risks associated with using digital tools safely. The findings also suggest that teachers with different levels of digital literacy have varying levels of understanding in areas such as copyright laws and collaboration.